Talent Management and Career Sustainability among Civil Servants in West Java's Education Department - Makii, Maki; Hayati, Neuneung Ratna (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze the role of talent management in supporting career sustainability and to examine the relationship between career growth and career sustainability, with talent management as a moderating variable, among civil servants (ASN) at Branch Office (KCD) XI of the West Java Provincial Education Office. The study employs a quantitative approach with an explanatory design. Data were collected through the distribution of a structured questionnaire using a five-point Likert scale to ASN selected via proportional random sampling. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that career growth has a positive and significant effect on career sustainability. Furthermore, talent management was found to positively and significantly moderate the relationship between career growth and career sustainability; thus, the implementation of effective talent management can strengthen the influence of career growth on the career sustainability of ASN. These findings indicate that strengthening the talent management system is a crucial strategy for supporting the career sustainability of public sector employees. This study provides an empirical contribution to the literature on talent management and career sustainability and offers insights for policymakers in optimizing human resource management within the West Java Provincial Education Office.